การพัฒนาชุดตรวจสอบคลอแรมเฟนิคอลโดยวิธีเอนไซม์ลิงค์อิมมูโนซอร์เบนต์แอสเสย์ - พรพิมล พันธุ์ธีรานุรักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Chloramphenicol (CAP) is an antibiotic substance widely used to treat bacterial infection in animal. Misuse of chloramphenicol may result in residues in meat or products from animals which directly affect consumer health. From this reason, the use of chloramphenicol in food producing animals is forbidden in many countries. Therefore, the detection of chloramphenicol residue in food is necessary. In this research, test kit prototype for chloamphenicol detection by using indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) was developed. The optimal concentration of coating antigen (CAP-BSA) on the microtiter plate and monoclonal antibodies specific for chloramphenicol was 0.1 ug/ml and 1 ug/ml, respectively. The developed test kit could quantitatively measure chloramphenicol in the range of 0.3-20 ng/ml. The percentages of coefficient variation (%(CV) of intra-assay and inter-assay were between 2.5-16.4% and 3.5-22.9%, repectively. In addition, the average of % recovery of spiked chloramphenicol in buffer and ground shrimp at several concentrations were 106% and 97%, respectively, which were comparable to the values quantified by the commercial test kit used in this research and LC-MS-MS method.